Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s12098-007-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between anemia and blood levels of iron, zinc, copper, cadmium and lead in children

Abstract: High copper, cadmium and lead decreased iron absorption and negatively affected hematological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 19 publications
10
53
1
2
Order By: Relevance
“…In our case, the mobile As pool in soils is represented by inorganic arsenate (Marin et al 1993) suggesting possible intensification of AsCu interaction. The other previously described interactions such as As-Fe (Paul et al 2002), Cd-Fe (Turgut et al 2007), or Cd-Cu (Chmielnicka and Sowa 1996) were not confirmed in our experiment. As already mentioned, the individual experiments differed in element dose and application, element source, and duration of the experiment.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In our case, the mobile As pool in soils is represented by inorganic arsenate (Marin et al 1993) suggesting possible intensification of AsCu interaction. The other previously described interactions such as As-Fe (Paul et al 2002), Cd-Fe (Turgut et al 2007), or Cd-Cu (Chmielnicka and Sowa 1996) were not confirmed in our experiment. As already mentioned, the individual experiments differed in element dose and application, element source, and duration of the experiment.…”
Section: Discussioncontrasting
confidence: 86%
“…For example, calcium and/or zinc deficiency can result in increasing resorption of lead and cadmium (Bencko et al 1995). Increased Cd, Cu, and Pb levels were observed in the blood of anaemic children (Turgut et al 2007). Similarly, daily rat exposition to 15 mg/kg CdCl 2 for 30 days resulted in anaemia followed by the changes in the metabolism and antioxidative activity of erythrocytes (Kostic et al 1993).…”
Section: Introductionmentioning
confidence: 95%
“…Similar effect was observed by Hiratsuka et al (1996) in rats intravenously exposed to Cd. Also Turgut et al (2007) described that high cadmium and lead decreased iron absorption and negatively affected hematological parameters. Except for lower Fe levels in the treated rat tissues, no significant changes in hematological parameters were registered in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…People can be exposed to toxic pollutants like lead, cadmium, mercury and arsenic through intake of polluted food and water or contact with contaminated dust, soil, or air (2).Cigarette smoking and alcohol intake can also increase lead levels in blood and seminal plasma (3,4,5). Deficiencies of dietary calcium, zinc and iron may increase lead level in blood as well (6,7,8).…”
Section: Introductionmentioning
confidence: 99%